Literature Review: The Relationship Between Malaria Infection And The Incidence Of Anemia - Adinda Pradana Putri; Syamsu Rijal; Windy Nurul Aisyah (International Medical Journal Corp. Ltd, 2025)
Malaria is an infectious disease caused by Plasmodium parasites, which are a primary cause of anemia. This review aims to analyze the correlation between Plasmodium species and the incidence of anemia through a literature review of studies conducted in Indonesia over the past five years. The results indicate that although both P. falciparum and P. vivax can cause anemia, a significant relationship between the Plasmodium species and the severity of anemia is not consistently found. This review emphasizes the importance of early monitoring of malaria infection to prevent hematological complications.